Essential Radiology for Sports Medicine - Robinson, Philip; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
This highly illustrated, practical book provides a systematic approach to the radiological assessment of all significant sports injuries. Imaging features are presented along with discussion of the influence of these findings on treatment and image-guided interventions. For each anatomical area, the underlying biomechanical features that produce injury are explored. All imaging modalities are featured, with emphasis on MRI, MR arthrography, CT, and ultrasound. A concise guide to sports injuries, this book will help clinicians quickly identify the appropriate imaging techniques to best serve their patients. This up-to-date resource is an excellent, high-yield resource for radiologists, emergency radiologists, orthopedists, and sports medicine professionals. International experts provide guidance as to how sports injuries occur and how to recognize relevant imaging findings.
Knee Injuries -- Hip, Pelvis and Groin Injuries -- Ankle and Foot Injuries -- Osseous Stress Injury in Athletes -- Shoulder Injuries -- Elbow Injuries -- Hand and Wrist Injuries -- Postoperative Imaging in Sports Medicine -- Muscle Injury and Complications -- Sports-Related Disorders of the Spine and Sacrum -- Ultrasound-Guided Sports Intervention.
Keywords: Medicine; Radiology, Medical; Interventional radiology; Orthopedics; Sports medicine; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Interventional Radiology; Sports Medicine; Orthopedics